Estudo das citações constantes das dissertações de mestrado em ciência da informação do IBICT/UFRJ - Rodrigues, Maria da Paz Lins (1981)
Analysis of two thousand three hundred and ten citations contained in sixty two dissertations presented by M.A. students of Information Science at "IBICT" between the years 1972 and 1979, in order to observe the standards of distribution and incidence; to determine the half-life of the mentioned literature; to establish the research front as well as to establish its group of elite and the impact factor of the authors. Periodical Literature makes up 48 por cento of the studied literature, books and pamphlets 27 por cento, and papers presented in professional meetings 10 por cento. The results of the analysis lead us to the following conclusions: a) Information Science is a new field where there is a great influence from the United States and so the periodical literature predominating is in the English Language; b) the dissertation try to keep up with the development of the area through research which tries to establish itself on the area of structure and flux of information what is a tendency of Information Science in Brazil; c) the emerging of Brazilians authors on the three bases of data studied, confirm the influence of the Master’s Degree in Information Science.